Role of chromatin remodeling complex SWI/SNF and VDR in chronic rhinosinusitis - Kowalik, Katarzyna; Waniewska-Leczycka, Martyna; Sarnowska, Elżbieta; Rusetska, Natalia; Sierdziński, Janusz; Zagor, Mariola (Advances in clinical and experimental medicine : official organ Wroclaw Medical University, 2020)
The SWI/SNF (SWItch/sucrose non-fermentable) chromatin remodeling complex enables glucocorticoid receptor (GR) and vitamin D receptor (VDR) to function correctly and is engaged in inflammation response. The SWI/SNF may play an important role in chronic rhinosinusitis (CRS). The aim of this study was to assess the following: 1) the gene and protein expression of the SWI/SNF complex subunits in sinonasal mucosa; 2) relation of SWI/SNF complex and VDR expression; and 3) correlation with clinical data. The study population consisted of 52 subjects with CRS without nasal polyps, 55 with CRS with nasal polyps and 59 controls. The SWI/SNF protein expression level was analyzed in immunohistochemical (IHC) staining. Human nasal epithelial cells (HNECs) was stimulated using lipopolysaccharide (LPS), Staphylococcal enterotoxin B (SEB) and vitamin D3 (vitD3) in vitro. The transcript level of the SWI/SNF subunits was measured with polymerase chain reaction (PCR). In the control group, the intensity of the IHC staining for SWI/SNF subunits was significantly higher than in both groups of patients with CRS (p < 0.05). A positive correlation of the SWI/SNF protein expression was noticed with VDR expression level (p < 0.043). Association between SWI/SNF protein expression level and allergy, neutrophils and body mass index (BMI) has been observed (p < 0.05). The decreased transcript level of the SWI/SNF subunits genes in HNECs was observed after LPS stimulation and increased after vitD3 stimulation. The SWI/SNF complex may influence CRS through steroid hormone signaling and VDR. Thus, modification in therapy may be mandatory in patients with CRS and altered SWI/SNF signaling, reflecting resistance to steroids treatment.